Multi-Stakeholder Evaluation of Dual-Qualified Humanities Teachers: A Case from a Chinese Applied University - OU, NU; Tunkiew, Somkiet; Chanboon, Somyos (Rajapark Journal, 2026)
This study examines (1) multi-stakeholder perceptions of competency demand and attainment among dual-qualified humanities teachers, (2) evaluation differences among faculty, departmental leaders, and administrative staff, and (3) mechanisms of stakeholder divergence based on an original cognition–process–institution framework. Conducted at a Chinese application-oriented university in Southeast China, the study involved a total sample of N = 79, using purposive and stratified sampling. Data were collected through questionnaires and interviews and analyzed using descriptive statistics, Gap analysis, ANOVA, t-tests, and content analysis. Findings reveal significant gaps between competency demand and attainment, indicating structural imbalances in teacher development. Practical competence is the most critical deficit. Distinct role-based evaluation patterns are observed across stakeholder groups. These divergences are explained through the cognition–process–institution framework, proposed as an original integrative model of evaluation misalignment and institutional governance.